2021
DOI: 10.2147/idr.s293290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antibiotic Resistance and Virulence Traits (Genetic and Phenotypic) in Klebsiella pneumoniae Clinical Isolates from Pakistan: Identification of Significant Levels of Carbapenem and Colistin Resistance

Abstract: Background:The emergence of carbapenem-resistant and hypervirulent hypermucoviscous Klebsiella pneumoniae strains poses a significant public health challenge. We determined the MDR profiles, antibiotic resistance factors, virulence gene complement, and hypermucoviscous features of 200 clinical K. pneumoniae isolates from two major tertiary care hospitals in Islamabad and Rawalpindi, Pakistan. Methods: Susceptibility profiling and phenotypic analysis were performed according to the CLSI guidelines. Genetic dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
6
21
5
Order By: Relevance
“…Additionally, nearly 40% resistance was determined against carbapenems, namely meropenem and imipenem. The minimum resistance was determined against colistin which was about 15%; however, 22% colistin resistance was determined in isolates collected in the present study (45). In comparison to the previous study conducted in Pakistan during 2010, this study reported 50% resistance to carbapenems which means a 50% MDR prevalence ratio, higher than previously noted (46).…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, nearly 40% resistance was determined against carbapenems, namely meropenem and imipenem. The minimum resistance was determined against colistin which was about 15%; however, 22% colistin resistance was determined in isolates collected in the present study (45). In comparison to the previous study conducted in Pakistan during 2010, this study reported 50% resistance to carbapenems which means a 50% MDR prevalence ratio, higher than previously noted (46).…”
Section: Discussioncontrasting
confidence: 82%
“…In the K. pneumoniae population, the median and IQR (25-75%) of the MIC were determined and expressed in mg/L in a log 2 box plot. As shown in Figure 1B, the bacterial population was mainly susceptible to Amk with a median (IQR) of 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Similar to Amk, the population was mainly susceptible to carbapenem, Imp, and Mer with a median of 1 (0.5-1) and 1 (0.5-2), respectively.…”
Section: Antibiotic Susceptibilitymentioning
confidence: 96%
“…The high MDR shown by strains of K. pneumoniae does not fully explain its notable success as one of the most important agents of HAIs, suggesting the participation of other factors [ 9 ]. An increasing number of authors suggest that increased bacterial survival during infections is related to virulence factors [ 1 , 3 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the K. pneumoniae population, the median and IQR (25-75%) of the MIC were determined and expressed in mg/L in a log2 box plot. As shown in Figure 1B, the bacterial population was mainly susceptible to Amk with a median (IQR) of 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Similar to Amk, the population was mainly susceptible to carbapenem, Imp, and Mer with a median of 1 (0.5 -1) and 1 (0.5 -2), respectively.…”
Section: Antibiotic Susceptibilitymentioning
confidence: 96%
“…The high MDR shown by strains of K. pneumoniae does not fully explain its notable success as one of the most important agents of HAIs, suggesting the participation of other factors [9]. An increasing number of authors suggest that increased bacterial survival during infections is related to virulence factors [1,3,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%